Thermo – photocatalytic production of hydrogen from water with methanol/formaldehyde as sacrificial agent under mild conditions - Nyamai, Nancy Akoth (University of the Witwatersrand, Johannesburg, 2024)
Fossil fuels are the main source of energy for modern society to this decade. The awareness of scarcity of fossil fuels and the environmental degradation accompanying their use has motivated researchers to conduct extensive research in other forms of energy for mitigation. Hydrogen has the potential to replace the traditional fuels for transportation application and other uses. Comparatively, hydrogen has higher energy (143 MJ/kg) than the conventional fossil fuels (natural gas: 53.6 MJ/kg, petrol: 46.4 MJ/kg, diesel: 45.4 MJ/kg) moreover, its environmental friendly as it produces water as the only by-product of its combustion. In spite of its superiority, public acceptance of hydrogen based technologies are still undermined. Following the main finding of water-based photo-electrolysis in 1972, scientists, engineers and environmental activists have intensified research on the production of hydrogen via photocatalytic water splitting adopting different modifications of semiconducting materials such as titanium dioxide, TiO2, cadmium sulphide, graphitic carbon nitride and using sunlight to fragment water molecules to produce hydrogen gas. Titanium is one of the most attractive d-block transition metals in use as water splitting photocatalyst. It is preferred because of its low density, high strength, corrosion resistance, availability and cost effectiveness. However, efficient water splitting using visible light and TO2 has been a challenge. TO2 has a setback of wide bandgap, 3.0 – 3.2 eV, which lowers its prospective for visible light absorption. This study outlines the development and the testing of efficient catalytic materials for the thermo-photocatalytic production of hydrogen from water. Methanol-water mixture was also tested under mild conditions. TiO2 composited with carbon nanofibers, CNFs at different loadings (0,10 and 20%) and co-catalysts platinum (Pt), gold (Au), iridium (Ir), zinc (Zn) and copper (Cu) were synthesized and used in the photocatalytic water splitting and appreciable quantities of hydrogen were obtained. Additionally, 10% methanol was also used as sacrificial reagent with water and tested for hydrogen evolution but the results were not significantly different when compared to the results obtained from the use of photocatalysts without methanol addition. The photocatalysts were tested for hydrogen production using water, and the most active photocatalyst, F_CNFs/20% _TiO2/6%Pt exhibited an activity of 0.45 mol g-1h-1. This was followed by F_CNFs/10% _TiO2/5%Au and F_CNFs/20% _TiO2/1%Ir with activities of 0.28 mol g-1h-1, and 0.21 mol g-1h-1 respectively. In another section of this study, the focus was on the fabrication of nanomaterials for advanced photocatalytic water splitting as a result, structures of TiO2/CNFs, Cu/TiO2/CNFs, and Zn/ TiO2/CNFs nanocomposites of mesoporous nature were synthesized using CNFs and surfactant wrapping sol-gel/hydrothermal method. Impregnation technique was used in copper and zinc loading while characterization of the synthesized catalysts was achieved by RD, Raman, FESEM, TEM, UV/DRS, BET, FTIR, XPS, and PL techniques. Water splitting was performed by UV light irradiation and the effect of compositing TiO2/CNFs-Cu/Zn evaluated. 10%_TiO2/CNFs/5%Zn composite was the most efficient photocatalyst for hydrogen production when compared with the rest of the samples. The most efficient photocatalyst, 10%_TiO2/CNFs/5%Zn, produced 0.53 mol (h g cat.)-1 of H2 which was 90-100 folds the amount generated over commercial TiO2 - P25, and pure TiO2 photocatalysts. The improved photo-activity of the TiO2/CNFs, Pt/TiO2/CNFs, Au/TiO2/CNFs, Ir/TiO2/CNFs, Cu/TiO2/CNFs, and Zn/ TiO2/CNFs composites were due to the synergistic effect between Pt, Au, Ir, Cu, Zn, and CNFs, greater BET surface area, suitable band structure and reduced recombination rate of the photo-generated charge carriers. This work gives promising route for fabricating TiO2/CNFs/metal (Pt, Au, Ir, Cu, and Zn) composites for advanced H2 production using UV- radiation.
A thesis submitted in fulfilment of the requirements for the Degree of Philosophy in Chemistry, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Photocatalytic water splitting; Renewable energy production; Catalysis; UCTD; SDG-7: Affordable and clean energy; SDG-13: Climate action